Obstructive shock caused by right atrial thrombosis secondary to malignant pheochromocytoma in a dog. Issue 9 (13th August 2020) - Robveille, C; Smart, L; Boyd, CJ
Abstract : Background: Obstructive shock can be caused by any lesion leading to extraluminal compression or intraluminal occlusion of the cardiac chambers or major vessels. Case Report: A 12‐year‐old, male castrated, Border Collie cross dog presented to a veterinary teaching hospital for collapse. A physical examination revealed severe vasoconstrictive shock and abdominal distension. Abnormalities on blood tests were consistent with systemic hypoperfusion. Cardiac underfilling, hepatomegaly with distended vasculature and ascites were identified by focused ultrasonography, raising suspicion of obstructive shock. This was supported by the radiographic findings of microcardia and a distended caudal vena cava (CVC). There was transient response to fluid therapy for blood volume expansion. Repeat focused ultrasonography during rapid intravenous fluid administration identified a right intra‐atrial mass, assessed as likely to be causing obstruction of venous return. The dog was humanely euthanased given the guarded prognosis. At postmortem evaluation, a malignant pheochromocytoma in the left adrenal gland with tumour thrombus extending to the tricuspid valve through the CVC was found. The extensive thrombus caused the obstructive shock in this case. Metastasis in a peripheral lymph node and neoplastic emboli in the heart and lungs were also visible at the histopathological evaluation. Conclusion: To the best of authors' knowledge, this is the first report of severe obstructive shock secondary to extension of caval tumour thrombus into the right atrium in a dog with malignant pheochromocytoma. Tumour thrombus from a malignant pheochromocytoma should be included as a differential diagnosis of obstructive shock, with or without a visible right intra‐atrial mass, in dogs. Serial focused ultrasonography during intravenous fluid administration can aid diagnosis.